German foreign intelligence from Hitler's war to the Cold War : flawed assumptions and faulty analysis - Hutchinson, Robert, 1986- (University Press of Kansas, 2019)
"Through a thorough evaluation of Nazi-era German intelligence reports, Robert Hutchinson reveals that, far from a haven of objective analysis on the margins of the Nazi dictatorship, German foreign intelligence agents repeatedly affirmed Hitler's misunderstanding of Great Britain, underestimated the Soviet Union, and downplayed the economic and military contribution of the United States to the widening war in Europe. Moreover, intelligence agents in these same reports were vocal in their identification and denunciation of the malevolent influence of international Jewry on world affairs. Hutchinson's revelation is additionally significant because, after 1945, many German intelligence figures found employment with the Cold War West, using their "expertise" in Soviet affairs to advise the West German government, US military, and CIA on Soviet military and political matters."--Provided by publisher